ANALISIS PELAYANANPADA PENDAFTARAN SERTIFIKAT JAMINAN FIDUSIA DI KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA JAWA TIMUR - YOSSI WAHYU ARIEANTO (Universitas Negeri Surabaya, 2013)
ANALISIS PELAYANANPADA PENDAFTARAN SERTIFIKAT JAMINAN FIDUSIA DI KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA JAWA TIMURYossi Wahyu ArieantoMeirinawatiAbsctractThe public service is the primary function of Government to fulfill the people’s needs of various aspects of the service. One aspect of concern currently is service on the registration of the fiduciary guarantee. Where the fiduciary guarantee is rights guarantee in the form of objects handing over rights based on the trust which agreed to guarantee repayment of the debt to the lender that serves to protect the rights of consumers who do a financing vehicle for credit finance companies. Finance companies must register the fiduciary guarantee in any credit financing of motor vehicles in the Ministry of Justice and Human Rights regional office, in accordance with Permenkeu Number 130/FMD. 010/2012. One of the regional offices that deliver a fiduciary guarantee services is the Ministry of Justice and Human Rights of East Java regional office. This research aims to analyze the service on the fiduciary guarantee certificate registration in the regional offices of the Ministry of Justice and Human Rights of East Java.The type of research that used is descriptive with qualitative approach. The subject of this research consists of the Head. Field of the Fiduciary service, staffs in the fiduciary service, and people that used the fiduciary service. Data collection techniques used are interviews, observation, and documentation. Technique of data analysis performed using analysis of qualitative data in the form of data reduction, the presentation of the data, and draw conclusions.The results of this research describe the service on registration of fiduciary guarantee, can be seen from the indicator of Procedure that appropriate service standard service and comprehension of the people and the officer was pretty good. settlement time, the Government’s defined standards could not be fulfilled by the officer. Service fees, there are Government-issued regulations about the cost of a fiduciary guarantee registration. Service product, there are three products that accepted by the community. They are Fiduciary guarantee certificate, the changes and removal of the fiduciary guarantee certificate. Infrastructure and facilities, including buildings, equipment and human resources, can be said to be inadequate. The Service provider's competence shown by the officers that had acted professionally and in accordance with proficiency.Keywords: Fiduciary guarantee, Public Service